Pendidikan Remaja Menurut Pandangan Islam - Sukatin; Qadafi, Muamar; Ariani, Septi; Patimah, Siti; Apriyanto, Reza (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
Islam is very important in directing or guiding youth. Various deviations committed by adolescents are several factors such as lack of good educational upbringing, lack of role models from the family, lack of attention from parents, so that teenagers do not behave like what is taught by Islam. Because during this adolescent period a person will experience emotional turmoil and instability, indecision in finding a handle on life and the adolescent's belief in God and religion will also be increasingly unstable if there is a difference between the values he learns and the behavior of people in society. Adolescence is a period of preparation to become a mature and healthy adult. Therefore, the responsibility of education lies with parents, teachers and the community to achieve the goals of youth education according to the Islamic view and achieve Islamic education. The purpose of this study is one of the efforts to find answers to the problems above, it is hoped that youth education from an Islamic viewpoint will guide adolescents so that youth remain mentally healthy, have noble character, have piety to Allah SWT and values that originate from the Koran and Sunnah. From the results of this study, the writer can conclude that education in Islam is so important that it is an obligation, because education can change people from not knowing to knowing. Specialized Education for youth.